1993
DOI: 10.1080/01919512.1993.10555736
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH NOTE: Ozone Degradation Of Selected Non-Agricultural Herbicides

Abstract: This research note investigates the efficiency of ozone for the degradation of threeherbicides,imazapyr[2-I4-isopropyl-4-methyI-Soxo-2-imidazolin-2-yll-nicotinic acidl, triclopyr (3,5,6-trichloro-2-pyridinyloxyacetic acidl and diuron [3-(3,4-dichlorophenyll-1,l-dimethylurea under controlled laboratory conditions. Experiments were conducted at pH 7.5, in a bubble contactor column, with a raw lowland surface water spiked with initial active ingredient concentrations of 2 pgl". The ozone doses applied and consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Byproducts formed included deethylatrazine and deisopropylatrazine. Lambert et al ( 1993) observed removals of 53, 48, and 90% for the herbicides imazapyr, triclopyr, and diuron, respectively, at pH 7.5 and an ozone dose of 4.8 mg/L, For ozonation of process streams, Beulker and Jekel ( 1993a and b) observed that ozonation of pulp mill eflluents at pH 2 reduced COD, DOC, and color, whereas ozonation at alkaline pH caused an increase in color. The color increase was thought to be due to the polymerization of organics.…”
Section: Oxidation /Reducfionmentioning
confidence: 98%
“…Byproducts formed included deethylatrazine and deisopropylatrazine. Lambert et al ( 1993) observed removals of 53, 48, and 90% for the herbicides imazapyr, triclopyr, and diuron, respectively, at pH 7.5 and an ozone dose of 4.8 mg/L, For ozonation of process streams, Beulker and Jekel ( 1993a and b) observed that ozonation of pulp mill eflluents at pH 2 reduced COD, DOC, and color, whereas ozonation at alkaline pH caused an increase in color. The color increase was thought to be due to the polymerization of organics.…”
Section: Oxidation /Reducfionmentioning
confidence: 98%
“…Ozone has recently received much attention in water treatment technology, due to its high capacity for oxidation and disinfection. The ozonation process is a proven technology for 2 removing various types of environmental pollutants, such as dyes, herbicides and other pesticides in aqueous solution [1][2][3]. It is well known that the reaction of ozone with organic substrates follows two reaction mechanisms [4]: (1) molecular ozone oxidation (direct reaction), and (2) free radical oxidation (indirect reaction).…”
Section: Introductionmentioning
confidence: 99%